Special edition using visual C++ 6 - Gregory, Kate. ([S.l.] : Que, 1998)
Special Edition Using Visual C++ 6 focuses on making you productive with Visual C++ as quickly as possible. Because of its straightforward approach, this book is able to progress into more advanced topics such as database capabilities, creating ActiveX controls and documents, and enterprise features. Coverage includes all the new features of version 6 as well as expanding on a few topics such as Active Server Pages, VC++, and ActiveX Data Object (ADO & OLE DB).